Ovarian Hyperstimulation Syndrome: Contemporary Approach to Pathophysiology, Risk Stratification, Prevention and Management - Tulic, Lidija; Katarina; Stojnic, Jelena; Micic, Jelena; Bila, Jovan; Ivanovic, Stefan; Dotlic, Jelena; Pilic, Igor; Sljivancanin, Dragisa; Tulic, Ivan (Medical Research, 2026)
Ovarian hyperstimulation syndrome (OHSS) is a potentially serious iatrogenic complication of controlled ovarian stimulation in assisted reproductive technology procedures. Despite substantial progress in stimulation protocols and preventive strategies, OHSS remains an important clinical and safety concern in contemporary IVF practice. The purpose of this narrative review is to summarize and critically analyze current knowledge regarding the pathophysiology, risk factors, clinical presentation, prevention, and management of OHSS. Relevant literature was identified through searches of the PubMed/MEDLINE, Scopus, and Web of Science databases, including clinical studies, cohort analyses, systematic reviews, and professional society guidelines published between 2019 and 2026, with selective inclusion of earlier landmark studies essential for understanding the basic mechanisms of the syndrome. Current evidence indicates that the key pathophysiological mechanism of OHSS is increased vascular permeability mediated by vascular endothelial growth factor (VEGF), most commonly triggered by exposure to human chorionic gonadotropin. Identification of high-risk patients using ovarian reserve biomarkers, individualized gonadotropin dosing, the use of GnRH antagonist protocols and GnRH agonist trigger, as well as freeze-all embryo strategies, have substantially reduced the incidence of moderate and severe forms of the syndrome. Contemporary management of OHSS is therefore primarily based on prevention and individualized stimulation strategies aimed at optimizing reproductive outcomes while ensuring maximal patient safety.